STRATEGIC INNOVATIONS IN SUSTAINABLE BUSINESS MODELS: A COMPARATIVE ANALYSIS OF LEADING GLOBAL COMPANIES - Shibli Jamal Shariff Asad; Maria Widyarini; Oki Sunardi (Business Administration Department - Universitas Katolik Parahyangan, 2024)
As problems associated with the environment, society, and economy become increasingly pressing, businesses face the need to consider sustainability as a core strategy. Thus, the current research seeks to explore strategic innovations in sustainable business models by analyzing the leading global organizations. The study used a qualitative methodology based on the analysis of documents comprising 87 cases selected from the extant literature and company reports. As found, firms can sustain their operations via altering value propositions, incorporating stakeholder views, and developing dynamic capabilities, which, in turn, allows them to apply design thinking and the concept of circular economy. In terms of patterns of innovation, the following can be distinguished: sustainable development of products and services, green supply chain, and sustainability-oriented marketing strategies. Moreover, the differences between various industries have been considered since they indicate the impact of context on sustainable business models' use. Overall, it can be concluded that strategic innovations play a key role in ensuring both sustainability success and competitive advantage.